Webinar Penyegaran Kader Posyandu; Update Isu dan Penanganan Masalah Gizi di Wilayah Kerja Desa Cibanteng Bogor - Tri Ardianti Khasanah; Mia Srimiati; Dea Triany Violeta; Maria Chitrawati (Jurnal Abdimas Kesehatan (JAK), 2022)
Posyandu is the spearhead and one of the community-based health efforts that has an important role in bringing promotive and preventive efforts closer to the community, especially efforts to improve the nutritional status of the community and maternal and child health. The achievement of monitoring growth in 2018 in Cibanteng Village was 76.5% with a target of 80%, in connection with these conditions it was deemed necessary to equalize perceptions and increase the ability/skills of posyandu cadres, especially the management of posyandu and posyandu cadres in the working area. The purpose of this community service is to provide refreshment and understanding of the main tasks of cadres in managing and carrying out minimal activities at posyandu. The target in this community service is the cadres of the Cibanteng Village working area. The results of community service indicate that the refresher for cadres in the Cibanteng Bogor Village Work Area has been going well, the interest and enthusiasm of the cadres are fully willing to carry out refresher knowledge, the implementation of the refresher is in accordance with the training objectives. The drawback is that the learning method in the implementation of the refresher is still relatively new and difficult for village cadres to understand, namely using the zoom webinar media